Pengembangan Alat Ukur Kepuasan Konsumen - Lia Purnamawati (Jurnal Psikologi Terapan, 2018)
All kinds of halal products in circulation that in Indonesia are widely used by consumers, one of them is cosmetics. It can be seen from several phenomena as well as the increasingly critical society in assessing the halalness of products that have been consumed, the growth of Islamic culture, and the rapid use of Muslim fashion on the development of modern-oriented lifestyles and refers to Islamic values. Respondents that can be obtained by the researchers by doing the main data retrieval amounted to 112 respondents who are all women. Age range of respondents from 18 to 24 years. Based on the results of research and analysis that has been done about consumer satisfaction Wardah cosmetic products at Malikussaleh University students, it is concluded that the scale of customer satisfaction developed in this study can be considered to have a good psychometric standard with alpha (α = 0.656) and the number of valid items as many as 15 items. It appears that the scale of customer satisfaction has constructive validity and internal consistency which is also good.